Stereoselective nucleophilic addition reactions to cyclic N-acyliminium ions using the indirect cation pool method: Elucidation of stereoselectivity by spectroscopic conformational analysis and DFT calculations - Mitsudo, Koichi; Yamamoto, Junya; Akagi, Tomoya; Yamashita, Atsuhiro; Haisa, Masahiro; Yoshioka, Kazuki; Mandai, Hiroki; Ueoka, Koji; Hempel, Christian; Yoshida, Jun-ichi; Suga, Seiji (Beilstein Journal of Organic Chemistry, 2018)
In this study, six-membered N-acyliminium ions were generated by the “indirect cation pool” method and reacted with several nucleophiles. These reactions afforded disubstituted piperidine derivatives with high diastereoselectivities and good to excellent yields. The conformations of the obtained N-acyliminium ions were studied by low temperature NMR analyses and DFT calculations and were found to be consistent with the Steven’s hypothesis.
Keywords: cation pool; conformation; electroorganic synthesis; N-acyliminium ion; NMR analysis; piperidine